Identification of human parvovirus 4 genotypes 1 and 2 in Chinese source plasma pools. Issue 8 (14th March 2021) - Jia, Junting; Zhong, Yadi; Zhang, Huan; Yuan, Dian; Ma, Limin; Wang, Deqing; Zhang, Jingang; Ma, Yuyuan
Abstract: Human parvovirus B19 (B19V) and human parvovirus 4 (PARV4) are known to infect humans and transmit through contaminated blood and blood products. Globally, three genotypes of B19V, as well as PARV4, have been identified, respectively. The existence of different B19V genotypes in Chinese plasma donors has been investigated, however,  the data regarding PARV4 were not available. The main objective of this study is to identify the genotypes of PARV4 circulating in Chinese plasma donors. By using a duplex quantitative polymerase chain reaction assay adapted for all genotypes of B19V and PARV4, 78 source plasma pools for fractionation were screened and quantified. Results showed that positive rates of B19V and PARV4 DNA in plasma pool samples were 25.64% and 14.10%, respectively. PARV4 sequences in two positive samples were next genotyped, and these two sequences belonged to PARV4 genotypes 1 and 2, respectively. In conclusion, the data present demonstrate the existence of PARV4 genotypes 1 and 2 in Chinese plasma donors for the first time and also show the relatively lower prevalence and level of PARV4 DNA in Chinese plasma donors in comparison with that of B19V DNA. Highlights: At least two PARV4 genotypes, 1 and 2, were currently present in China. The prevalence and level of PARV4 DNA in Chinese plasma donors were relatively lower in comparison with that of B19V DNA. The rate of B19V and PARV4 coinfection in Chinese source plasma pools was low.